To solve the given quadratic equation \( x^2 - 18x = -80 \), we'll first convert it into the form desired for Part A and then move on through the parts systematically.
Part A
We want to find a value of \( c \) such that the equation \( x^2 - 18x + c = -80 + c \) becomes a perfect square trinomial.
To complete the square for the expression \( x^2 - 18x \):
- Take half of the coefficient of \( x \) which is \(-18/2 = -9\).
- Square that result: \( (-9)^2 = 81 \).
Thus, \( c = 81 \) will make the left side a perfect square trinomial.
Part B
Now we rewrite the equation adding \( c \): \[ x^2 - 18x + 81 = -80 + 81 \] which simplifies to: \[ x^2 - 18x + 81 = 1 \]
Now, factoring the left-hand side we get: \[ (x - 9)^2 = 1 \]
Part C
Now we solve the equation \( (x - 9)^2 = 1 \).
Take the square root of both sides:
- \( x - 9 = 1 \) or
- \( x - 9 = -1 \)
Solving these:
- \( x = 10 \)
- \( x = 8 \)
The lesser number is \( x = 8 \).
Part D
The greater number is \( x = 10 \).
Summary of Answers:
- Part A: \( c = 81 \)
- Part B: \( (x - 9)^2 = 1 \)
- Part C: \( 8 \)
- Part D: \( 10 \)